Rozwiązane

1. Oblicz:
a) 4 +3.0
b) 3:(
2-11) -1 =
2. Oblicz
(-3):(1+3) =
3. Oblicz. Wynik przedstaw w najprostszej postaci.
a) + } -
b) 1 +2 -
e) 1.3 =
) 1.2
b) 2:15 -
d) 3 - 1 -
1) 2 - 15 15
3) (1} +110):13 =
4. Oblicz:
a) (1 : 3):13 =
b) 3:(
2-1) =​



1 Oblicza 4 30b 3211 1 2 Oblicz313 3 Oblicz Wynik Przedstaw W Najprostszej Postacia B 1 2 E 13 12b 215 D 3 1 1 2 15 153 1 11013 4 Oblicza 1 313 B 321 class=

Odpowiedź :

Odpowiedź:

Zad 1

[tex]a)4+3\frac{2}{3}*\frac{3}{10}=4+\frac{11}{3}*\frac{3}{10}=4+\frac{11}{10}=5\frac{1}{10}[/tex]

[tex]b)3\frac{3}{4}:(2\frac{4}{5}-1\frac{3}{10})-\frac{3}{4}=\frac{15}{4}:(2\frac{8}{10}-1\frac{3}{10})-\frac{3}{4}=[/tex]

[tex]\frac{15}{4}:1\frac{5}{10}-\frac{3}{4}=\frac{15}{4}*\frac{2}{3}-\frac{3}{4}=[/tex]

[tex]\frac{10}{4}-\frac{3}{4}=\frac{7}{4}=1\frac{3}{4}=1,75[/tex]

Zad 2

[tex](\frac{3}{5}-\frac{1}{3}):(1+\frac{1}{3})=(\frac{9}{15}-\frac{5}{15}):1\frac{1}{3}=\frac{4}{15}*\frac{3}{4}=\frac{1}{5}[/tex]

Zad 3

[tex]a)\frac{2}{5}+\frac{1}{2}=\frac{4}{10}+\frac{5}{10}=\frac{9}{10}=0,9[/tex]

[tex]b)1\frac{3}{4}+2\frac{5}{6}=1\frac{9}{12}+2\frac{10}{12}=3\frac{19}{12}=4\frac{7}{12}[/tex]

[tex]c)\frac{7}{8}-\frac{1}{6}=\frac{42}{48}-\frac{8}{48}=\frac{34}{48}=\frac{17}{24}[/tex]

[tex]d)3\frac{1}{4}- 1\frac{2}{3}=3\frac{3}{12}-1\frac{8}{12}=2\frac{15}{12}-1\frac{8}{12}=1\frac{7}{12}[/tex]

[tex]e)1\frac{2}{7}*3=\frac{9}{7}*3=\frac{27}{7}=3\frac{6}{7}[/tex]

[tex]f)1\frac{2}{5}*2\frac{1}{7}=\frac{7}{5}*\frac{15}{7}=3[/tex]

[tex]g)\frac{2}{5}:3=\frac{2}{5}*\frac{1}{3}=\frac{2}{15}[/tex]

[tex]h)2\frac{1}{4}:1\frac{1}{2}=\frac{9}{4}*\frac{2}{3}=\frac{3}{2}=1\frac{1}{2}[/tex]

[tex]i)2\frac{4}{5}-1\frac{1}{8}*1\frac{1}{3}=2\frac{4}{5}-\frac{9}{8}*\frac{4}{3}=2\frac{4}{5}-\frac{3}{2}=2\frac{8}{10}-1\frac{5}{10}=1\frac{3}{10}=1,3[/tex]

[tex]j)(1\frac{1}{2}+1\frac{3}{10}):1\frac{2}{5}=(1\frac{5}{10}+1\frac{3}{10})*\frac{5}{7}=\frac{28}{10}*\frac{5}{7}=\frac{20}{2}=2[/tex]

Zad 4

[tex]a))(1\frac{4}{5}:\frac{3}{7}):1\frac{2}{5}=(\frac{9}{5}*\frac{7}{3})*\frac{5}{7}=\frac{21}{5}*\frac{5}{7}=3[/tex]

[tex]b)3\frac{3}{4}:(2\frac{1}{6}-1\frac{1}{2})=\frac{15}{4}:(2\frac{1}{6}-1\frac{3}{6})=\frac{15}{4}:\frac{2}{3}=\frac{15}{4}*\frac{3}{2}=\frac{45}{8}=5\frac{5}{8}[/tex]

Szczegółowe wyjaśnienie: